Re-description and Proposed Reclassification of Myxilla (Burtonanchora) lacunosa Lambe, 1893 - Ott, Bruce; Reiswig, Henry M. (Zootaxa, 2019)
Lambe described Myxilla lacunosa from a specimen from Vancouver Island. Lambe’s sponge was subsequently placed in the subgenus Burtonanchora based on Lambe reporting smooth styles. A number of investigators, including the authors of this paper, report some styles with spines in Lambe’s sponge. We redescribe Myxilla lacunosa based on re-examination of Lambe’s holotype, and propose to place it in subgenus Myxilla based on the presence of spined styles rather than subgenus Burtonanchora which is defined as genus Myxilla with smooth styles.